Further Studies on the Hypercoagulable State of Patients with Cushing’s Syndrome - Patrassi, G M; Zanon, R Dal Bo; Boscaro, M; Martinelli, S; Girolami, A (Thrombosis and Haemostasis, 1985)
Factors XII, XI, IX and VIII, plasminogen and alpha2-antiplasmin levels were found to be increased in a group of patients affected by Cushing’s syndrome. High activity of these coagulation factors could be due to their increased release and synthesis mediated by cortisol. A significant correlation between the main arterial pressure and either factor VIII antigen, ristocetin cofactor or factor XII activity was found. Moreover a similar correlation between factor XII activity and either factor VIII antigen or ristocetin cofactor was seen. In conclusion, the presence of a hypercoagulable state in Cushing’s syndrome seems confirmed. Synergic release of factor XII and factor VIII from endothelium could be due to high blood vessel tone secondary to hypercorticism. Finally, decreased fibrinolytic activity was suspected according to plasminogen and alpha2-antiplasmin increase.
Keywords: Cushing’s syndrome; Hypercoagulable state; Hypertension